Дослідження середньовічного кургану поблизу с. Тепениця (до питання про кургани з кам'яними конструкціями у Середньому Подніпров'ї) - Петраускас, А.В.; Бібіков, Д.В.; Івакін, В.Г.; Павленко, С.В. (Археологія і давня історія України, 2019)
У статті публікуються результати досліджень кургану з кам'яною обкладинкою у насипі, здійснені Житомирською експедицією на курганному могильнику поблизу с. Тепениця Олевського району у 2015 р. Подається історія досліджень курганів із кам'яними конструкціями в насипі на території Середнього Подніпров'я (у Житомирському Поліссі та на Пороссі). Розглянуті основні гіпотези щодо походження не характерної для слов'янської й давньоруської поховальної обрядовості традиції обкладання камінням курганних насипів та етнічної приналежності населення, що залишило після себе дані пам'ятки. In the summer of 2015, Zhytomyr expedition conducted archaeological research at the burial mounds at the tract of Long Niva near the village Tepenitsa Olevsky district of Zhytomyr region. As a result, the burial with a stone construction under the embankment was explored and studied. The stone cover was discovered right after the turf layer and completely covered the embankment as if it was an armor. The construction consisted of granite fragments and pieces of quartzite and sandstone. At the bottom of the embankment were stone boulders of large size that became smaller at the top of burial. At the level of the mainland around the embankment placed small ditch that had a form of two arcuate sections. Remains of a skeleton or gravel pit in the burial mound was not discovered (cenotaph). Two large fragments of the potter’s pot was found on the sand pit in the central part of the embankment at the level of the ancient horizon. The practical absence of inventory does not allow date the archaeological complex clearly. A fragment of the pot can be attributed to two chronological periods: the end of IX — the first half of the X century or the second half of the XIII — XIV centuries.